Point mutations in the tyrosine kinase domain release the oncogenic and metastatic potential of the ron receptor - Santoro, Massimo Mattia; Penengo, Lorenza; Minetto, Marta; Orecchia, Sara; Cilli, Michele; Gaudino, Giovanni (Oncogene, 1998)
Ron (the receptor for Macrophage Stimulating Protein) has never been implicated before in human malignancies or in cell transformation. In this report we show that Ron can acquire oncogenic potential by means of two amino acid substitutions-D1232V and M1254T-affecting highly conserved residues in the tyrosine kinase domain. The same mutations in Kit and Ret have been found associated with two human malignancies, mastocytosis and Multiple Endocrine Neoplasia type 2B (MEN2B), respectively. Both mutations caused Ron-mediated transformation of 3T3 fibroblasts and tumour formation in nude mice. Moreover, cells transformed by the oncogenic Ron mutants displayed high metastatic potential. The Ron mutant receptors were constitutively active and the catalytic efficiency of the mutated kinase was higher than that of wild-type Ron. Oncogenic Ron mutants enhanced activation of the Ras/MAPK cascade with respect to wild type Ron, without affecting the JNK/SAPK pathway. Expression of Ron mutants in 3T3 fibroblasts led to different patterns of tyrosine-phos-phorylated proteins. These data show that point mutations altering catalytic properties and possibly substrate specificity of the Ron kinase may force cells toward tumorigenesis and metastasis.